OPTIMIZATION OF PHASOR MEASUREMENT UNIT PLACEMENT USING SEVERAL PROPOSED CASE FACTORS FOR POWER NETWORK MONITORING - BABA, MAVEEYA (2021)
Currently, the new state of the power system relies on precise monitoring of electrical quantities such as voltage and current phasors. Its operation disturbs because of the flicking in load and generation which may result in the interruption of the power supply or may cause catastrophic failure